Association of different biochemicals in the estrual genital discharge with pregnancy in Jersey crossbred cows - SOOD, PANKAJ; BHAVNA, BHAVNA; KUMAR, RAVI; VERMA, MADAN; SANKHYAN, VARUN; SINGH, M M (The Indian Journal of Animal Sciences, 2013)
The present study was conducted in 140 estrous periods in Jersey crossbred cows (122 in 111 normal (N) and 18 in 10 repeat breeders (RB) cows) that were inseminated. The N cows that conceived were classified to be in fertile estrus (FE); the others as non-fertile estrus (NFE) respectively. The N cows were investigated during estrus for body condition score, milk yield, extent of uterine tone, physical properties of genital discharge (color, viscosity and spinbarkait) and uterine tone. In addition, glucose (26 estrous periods), Na, K, Ca, Zn, Fe, Cu, Mg (96 estrus periods), P and total protein (122 estrus periods) were also estimated in the pre AI estrual genital discharge, in the N cows. Except for glucose, all other biochemicals were also estimated in the RB cows. Higher Zn in the FE versus NFE (1.5±0.2 versus 0.8±0.05 mg/ dl) and tendency for a higher K in the FE/NFE versus RB (48.0±4.0/46.0±2.7 mg/dl versus 37.4±3.1 mg/dl) and higher Ca in the FE versus RB (5.7±0.4 versus 4.0±0.5 mg/dl) cows were the salient features of the cows getting pregnant. Biochemical analysis of the genital discharge during 20 recurrent estrus periods revealed consistently higher Mg in the 9 FE (13.2±2.3 mg/dl) than the immediately preceding 9 NFE (5.8±0.9 mg/dl) periods in the N cows, whereas, the remaining 1 cow had identical Mg (3.8 mg/dl) during the non-fertile and fertile estrus. A similarity in body condition, milk yield, genital discharge and uterine tone at the time of AI between different groups of cows adds weight to the current findings. The correlation matrix between different biochemicals revealed that in spite of established antagonism in blood; some mineral combinations, more so in the FE cows, exhibited a positive correlation.